The Return of Women to the First Segment of School Education for Youth and Adults in Porto Velho, Rondônia - Falcão, Kary Jean (2019)
The objective of this study is to present challenges and perspectives on the return of women to the first segment of School Education for Youth and Adults (EJA), offered in night schools of the municipal school network. The research was conducted with 48 women, between 15 and 65 years of age, in four public schools of Porto Velho, located in different areas of the city. The study showed that factors preventing these women from going to school remain related to family factors such as their husbands’ prohibition of studying, concerns about the raising and care of their children, and household chores. As for the return of these women to school, the main difficulties encountered in the study were the concern about their children in relation with drug involvement and crime, work fatigue, old age and lack of security in the city’s neighborhoods.